Comparison of effects of desflurane and sevoflurane on postoperative nausea, vomiting, and pain in patients receiving opioid-based intravenous patient-controlled analgesia after thyroidectomy: Propensity score matching analysis. Issue 16 (April 2017) - Yoon, Il Jae; Kang, Hyun; Baek, Chong Wha; Choi, Geun Joo; Park, Yong-Hee; Jung, Yong Hun; Woo, Young Cheol; Lee, Sangseok
Abstract : Abstract: In this study, we aimed to compare the effect of desflurane and sevoflurane on postoperative nausea and vomiting and pain in patients receiving opioid-based intravenous patient-controlled analgesia (IV-PCA) after thyroidectomy. We reviewed the electronic medical records of 1042 patients administered opioid-based IV-PCA after a thyroidectomy at Chung-Ang University Hospital between January 1, 2010 and June 30, 2016. We classified the patients into 2 groups according to the inhalation anesthetic used for anesthesia: desflurane versus sevoflurane (groups D and S, n = 587 and 455, respectively). Then, propensity scoring was used to select 234 matched subjects between both groups based on their confounding factors. A propensity score matching method was used to match patients from the 2 groups in a 1:1 ratio. Before the propensity score analysis, there was no significant difference between the 2 groups. However, after the propensity score matching, the frequency of complete remission (CR, defined as no nausea and vomiting) was significantly higher in group S than it was in group D. The number of patients administered rescue antiemetics on day 0 in group S was lower than that in group D, although it was not statistically significant. In patients receiving opioid-based IV-PCA after thyroidectomy, sevoflurane seems to be more beneficial in achieving CR than desflurane was. However, further randomized controlled studies are needed to confirm this conclusion.